PosiDAF for algae removal - Henderson, Rita Kay (Cranfield University, 2007)
During algac blooms, coagulation is frequently unsuccessful resulting in poor flotation duc to complex algal character. 11iis thesis cxplorcs tlic link between algal character and conventional treatment and the potential for developing morc appropriatc algac trcatmcnt tcclinologics. Specifically, dissolvcd air flotation (DAF) that has bccn adaptcd by dosing cationic clicmicals to the saturator to modiry bubbic surfaccs, such that it docs not rcly on coagulation, is invcstigatcd. 1'his proccss is tcrmcd PosiDAF. Analysis of dissolved algogcnic organic mattcr (AOM) extracted from problcmatic species enabled investigation of the impact of morphology and AOM on coagulation- flocculation-flotation. Both increasing surface area and charge density of algae systcrns, werc rclatcd to increasing coagulant dcmand. Application of the appropriate coagulant dcmand ensured removal of all thrcc components - cclls, AOM and coagulant. Maintaining the zcta potential bct-%vccn -10 mV and +2 mV ensured optimum rcmoval was obtained. PosiDAF trials were conducted by dosing chemicals that had previously been shown to alter bubble charge, including co3gulant, surfactant and polymer, to the saturator. Coagulants were unsuitable for use in PosiDAF as they did not remain at the bubble surface. Highly hydrophobic, cationic surfactants were observed to remove cells according to a theoretical model, such that removal improved with increasing bubbic: particic ratio and with cell size. The polymer, polyDADNIAC, achieved greater removal cfficiencies than those predicted theoretically, attributed to an increase in the swept volume of the bubble. However, polyDADMAC was sensitive to changes in AOM composition. A chemical that combines attributes of both surfactant and polyDADMAC may overcome the barriers to PosiDAF implementation.